(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
This research aims to prepare samples of garnet ferrite Dy₃Fe₅O₁₂ doping with Ni – content (x=0.00;0.15; 0.25; 0.35; 0.45; 0.50) using the ceramic method. Then, we used the Nelson Riley method for determining lattice parameter a which has an important role to estimate the theoretical X-ray density and the stiffness modulus. In addition, the IR spectra have been taken and their data correlated with the mechanical properties of these samples.